2021
DOI: 10.1177/02654075211038624
|View full text |Cite
|
Sign up to set email alerts
|

Sexual destiny and growth beliefs, yuan beliefs, approach sexual motives, and sexual communication in Chinese heterosexual adults

Abstract: The current research examined the relationships between sexual implicit (destiny and growth) beliefs and yuan beliefs. This research also examined the association between sexual implicit beliefs and sexual communication satisfaction through the mediating role of sexual communal motives and motivation to express emotional value for a partner during sex. Results showed that sexual destiny and growth beliefs were positively related to yuan beliefs. Sexual destiny and growth beliefs were also associated with sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…Recently, several additional scholars have examined sexual beliefs (Cultice et al, 2022; Muise et al, 2018; Raposo et al, 2021; Rossi et al, 2022; Wu & Zheng, 2022) or how implicit beliefs are associated with sexuality (Bohns et al, 2015; Sutherland & Rehman, 2018). They have found that these sexual beliefs are linked to the couple relationship in a variety of ways, including associations with sexual communication (Wu & Zheng, 2022), sexual functioning (Raposo et al, 2021), sexual satisfaction (Rossi et al, 2022), and harmonious sexual passion (Hannah‐Walker & Busby, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, several additional scholars have examined sexual beliefs (Cultice et al, 2022; Muise et al, 2018; Raposo et al, 2021; Rossi et al, 2022; Wu & Zheng, 2022) or how implicit beliefs are associated with sexuality (Bohns et al, 2015; Sutherland & Rehman, 2018). They have found that these sexual beliefs are linked to the couple relationship in a variety of ways, including associations with sexual communication (Wu & Zheng, 2022), sexual functioning (Raposo et al, 2021), sexual satisfaction (Rossi et al, 2022), and harmonious sexual passion (Hannah‐Walker & Busby, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although sexual growth and destiny beliefs are relatively novel constructs, research suggests that they are linked with many important relationship processes (Cultice et al, 2022; Maxwell et al, 2017; Muise et al, 2018; Raposo et al, 2021; Rossi et al, 2022; Wu & Zheng, 2022). Growth and destiny beliefs are associated with variables such as sexual and relationship satisfaction (Hannah‐Walker & Busby, 2021; Rossi et al, 2022), personality traits of conscientiousness or openness, compatibility, levels of attachment‐related anxiety and avoidance, types of sexual passion (Hannah‐Walker & Busby, 2021), the importance of sex to each partner, and willingness to make sexual accommodations (Maxwell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations